Religious women and the problem of anger - Kenel, Mary Elizabeth (Journal of religion and health, 1988)
The experience of anger and its expression are sources of difficulty in the lives of many religious women. This article examines the circumstances that engender anger at the interpersonal and institutional levels. Elements that have assisted religious in coming to a mature integration of anger at the interpersonal-religious community levels are noted; the advantages and limitations of support groups are examined; and several techniques for coping with anger are indicated. The ability to transcend anger through the achievement of forgiveness is explored.